Contents of non-structural carbohydrates in fruiting cape gooseberry (Physalis peruviana L.) plants (2015)
Although the cape gooseberry has become the second most important export fruit in Colombia, information is scarce for its carbohydrate partitioning, which plays a major role in plant productivity. Seed-propagated Colombia ecotypes were kept in a greenhouse in 2.5-L plastic containers filled with washed quartz sand and were ferti-irrigated. The plants were pruned to one main vegetative stem with two generative stems. Dry matter (DM) partitioning during the initial plant growth showed the highest accumulation rate in the roots during the first 20 days, whereas, at a later stage of development, the shoot DM gain was higher and the leaf DM gain was lower than that of the roots. Sixty days after transplant, the plant parts were quantified and analyzed for glucose, fructose, sucrose, and starch. The roots were the largest carbohydrate pool for starch, but the sucrose content was lower in the roots than in the vegetative stem and the lower part of the reproductive stems. At 5-15 cm of the vegetative stem base, 6.4 mg of starch, 1.4 mg of monosaccharides and 5.3 mg/100 g of DM sucrose were found, indicating that this lower organ is also important for starch accumulation and, especially, for sucrose transport. In the two reproductive stems, the starch contents were much higher in the base part than in the apical part; the same relationship was found in the leaves. The monosaccharide content was the highest in the apical stem position with 8.2 mg/100 g DM. In contrast, the apical-positioned 10-day-old fruits had maximum starch concentrations (11.6 mg/100 g DM), possibly due to the assimilatory starch from green fruit photosynthesis, whereas the mature basal fruits (60-day-old) mainly accumulated sucrose (25.7 mg) and monosaccharides (21.2 mg/100 g DM).